2022
DOI: 10.1111/gcb.16292
|View full text |Cite
|
Sign up to set email alerts
|

Body size responses to the combined effects of climate and land use changes within an urban framework

Abstract: Alterations in body size can have profound impacts on an organism's life history and ecology with long-lasting effects that span multiple biological scales. Animal body size is influenced by environmental drivers, including climate change and land use change, the two largest current threats to biodiversity. Climate warming has led to smaller body sizes of many species due to impacts on growth (i.e., Bergmann's rule and temperature-size rule). Conversely, urbanization, which serves as a model for investigating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 195 publications
0
6
0
Order By: Relevance
“…Like those of most other ectotherms [ 67 , 105 , 106 ], anuran life-history traits (e.g., age at sexual maturity, mean age, and longevity) vary with environmental conditions [ 66 , 82 , 107 , 108 ]. For instance, populations experiencing longer growth seasons have younger ages at sexual maturity, mean age, and longevity than populations experiencing shorter growth seasons in previous studies that discussed geographical variation in B. andrewsi age structure [ 22 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Like those of most other ectotherms [ 67 , 105 , 106 ], anuran life-history traits (e.g., age at sexual maturity, mean age, and longevity) vary with environmental conditions [ 66 , 82 , 107 , 108 ]. For instance, populations experiencing longer growth seasons have younger ages at sexual maturity, mean age, and longevity than populations experiencing shorter growth seasons in previous studies that discussed geographical variation in B. andrewsi age structure [ 22 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The skeletochronology was used to estimate the ages of each sampled individual [ 22 ]. To produce histological sections for age determination, we used paraffin sectioning and Harris’s haematoxylin staining (see details in [ 66 , 97 ]). With a LEITZ dialux 40 microscope, we selected the cross-sections of the phalanx that had the smallest medullar cavity and the thickest cortical bone (13 m thick) to count the lines of arrested growth (LAG).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Climate warming has been suggested as the driver of observations of size shifts in several taxa including invertebrates (Polidori et al, 2020; Tseng et al, 2018), fish (Forster et al, 2012), amphibians (Caruso et al, 2014), birds (Prokosch et al, 2019), and mammals (Ozgul et al, 2009; Yom‐Tov et al, 2010). Body size is a fundamental trait for any organism that affects all physiological and ecological processes including the structuring of consumer–resource interactions (Martin & Sheridan, 2022). For example, Polidori et al (2020) suggested shrinking sizes of social wasps ( Dolichovespula sylvestris ) could lead to reduced foraging distances and the exclusion of large prey items previously accessible.…”
Section: Physiological and Phenotypic Pathwaysmentioning
confidence: 99%